KONSEP STRATEGI PEMBELAJARAN DAN APLIKASINYA - Santinah, Santinah (Holistik: Journal for Islamic Social Sciences, 2016)
Learning strategies are as a teacher effort in creating a system environment that allows students to learn or act of selection patterns of student teachers in the embodiment of teaching and learning activities . Criteria in selecting the learning strategies among other things , learning objectives , skills required subject matter , the media used , and the evaluation system to be used , as well as students as subjects and teachers practice. Keywords : Learning Strategies , teachers and students.